179k views
4 votes
Show work and explain with formulas.

4. If a_6 = 18 and a_13 = 32, find the sum of the 13 terms in an arithmetic sequence.

5. Find the sum (see picture).

6. Find the first three terms of the arithmetic series: a_1 = 17, a_n = 197, S_n = 2247


Show work and explain with formulas. 4. If a_6 = 18 and a_13 = 32, find the sum of-example-1
User Gilesc
by
5.3k points

1 Answer

1 vote

Answer:


\large\boxed{4.\ S_(13)=260}


\large\boxed{5.\ \sum\limits_(k=1)^7(2k+5)=91}


\large\boxed{6.\ a_1=17,\ a_2=26,\ a_3=35}

Explanation:

4.

We have:


a_6=18,\ a_(13)=32

These are the terms of the arithmetic sequence.

We know:


a_n=a_1+(n-1)d

Therefore


a_6=a_1+(6-1)d\ \text{and}\ a_(13)=a_1+(13-1)d\\\\a_6=a_1+5d\ \text{and}\ a_(13)=a_1+12d\\\\a_(13)-a_6=(a_1+12d)-(a_1+5d)\\\\a_(13)-a_6=a_1+12d-a_1-5d\\\\a_(13)-a_6=7d

Substitute a₆ = 18 and a₁₃ = 32:


7d=32-18


7d=14 divide both sides by 7


d=2


a_6=a_1+5d


18=a_1+5(2)


18=a_1+10 subtract 10 from both sides


8=a_1\to a_1=8

The formula of a sum of terms of an arithmetic sequence:


S_n=(a_1+n_1)/(2)\cdot n

Substitute a₁ = 8, a₁₃ = 32 and n = 13:


S_(13)=(8+32)/(2)\cdot13=(40)/(2)\cdot13=20\cdot13=260

===========================================

5.

We have


\sum\limits_(k=3)^7(2k+5)\to a_k=2k+5

Calculate
a_(k+1)


a_(k+1)=2(k+1)+5=2k+2+5=2k+7

Calculate the difference:


a_(k+1)-a_k=(2k+7)-(2k+5)=2k+7-2k-5=2

It's the arithmetic sequence with first term


a_1=2(1)+5=2+5=7

and common difference d = 2.

The formula of a sum of terms of an arithmetic sequence:


S_n=(2a_1+(n-1)d)/(2)\cdot n

Substitute n = 7, a₁ = 7 and d = 2:


S_7=(2(7)+(7-1)(2))/(2)\cdot7=(14+(6)(2))/(2)\cdot7=(14+12)/(2)\cdot7=(26)/(2)\cdot7=(13)(7)\\\\S_7=91

===========================================

6.

We have:


a_1=17,\ a_n=197,\ S_n=2247

The formula for the n-th term of an arithmetic sequence:


a_n=a_1+(n-1)d

The formula of the sum of terms of an arithmetic sequence:


S_n=(2a_1+(n-1)d)/(2)\cdot n

Substitute:


(1)\qquad 197=17+(n-1)d\\\\(2)\qquad2247=((2)(17)+(n-1)d)/(2)\cdot n

Convert the first equation:


197=17+(n-1)d subtract 17 from both sides


180=(n-1)d Substitute it to the second equation:


2247=(34+180)/(2)\cdot n\\\\2247=(214)/(2)\cdot n


2247=107n divde both sides by 107


21=n\to n=21

Put the value of n to the equation (n - 1)d = 180:


(21-1)d=180


20d=180 divide both sides by 20


d=9

Therefore we have the explicit formula for the nth term of an arithmetic sequence:


a_n=17+(n-1)(9)\\\\a_n=17+9n-9\\\\a_n=9n+8

Put n = 1, n = 2 and n = 3:


a_1=9(1)+8=9+8=17\qquad\text{CORRECT :)}\\\\a_2=9(2)+8=18+8=26\\\\a_3=9(3)+8=27+8=35

User Andreia
by
6.4k points